THE RELEVANCE OF THE PLANNING STRATEGY FOR THE IMPLEMENTATION OF SHARIA ACCOUNTING TOWARDS THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 AND SOCIETY 5.0 BY AL JAM'IYATUL WASHLIYAH - Burhanuddin Al-Butary; Safaruddin Siregar (el-Amwal, 2022)
The civilization of the world of science and technology is now heading towards the era of industrial revolution 4.0 and society 5.0, it takes the readiness of the world community to be able to deal with it. Indonesia, the majority of the population is Muslim, there are many Islamic organizations, one of which is Al Jam'iyatul Washliyah. This study aims to explore the relevance of Al Jam'iyatul Washliyah's planning strategy for the implementation of Islamic Accounting towards the industrial era 4.0 and society 5.0. The methodology used is a literature study approach to national and international journal articles, as well as books and other literature related to Islamic accounting. This research shows that on the one hand PT. BPRS Al-Washliyah has implemented sharia accounting in its operations. On the other hand, the Al-Washliyah organization organizationally still needs to further strengthen its strategy in order to fully implement sharia accounting in accordance with sharia PSAK. The results of this study are that the Islamic community organization which is classified as large in Indonesia is expected to be a model for the rise of a work system based on sharia. Islamic accountants and accounting are the answer to all forms of work in the accounting field that can respond to the challenges of modern times in the era of the industrial revolution 4.0 and society 5.0. Al-Washliyah needs to implement a strategy for implementing sharia accounting, because this is in accordance with Islamic teachings.